Undoing slavery : bodies, race, and rights in the age of abolition - Brown, Kathleen M., 1960- (Early American studies., 2023)
"Undoing Slavery excavates cultural, political, medical, and legal history to understand the abolitionist focus on the body on its own terms. Motivated by their conviction that the physical form of the human body was universal and faced with the growing racism of eighteenth and nineteenth century science, abolitionists in North America and Britain focused on undoing slavery's harm to the bodies of the enslaved. Their pragmatic focus on restoring the bodily integrity and wellbeing of enslaved people threw up many unexpected challenges. This book explores those challenges"--